Implementing the Eisenhower Matrix to Enhance Financial Stability and Optimize Learning Concentration: A Case Study of Mahasantri - Mohammad Rofiuddin; Achmad Istighfaransyah; Adnanda Harun Yahya (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2026)
Mahasantri students who simultaneously pursue higher education while living in Islamic boarding schools face dual financial pressures that may trigger psychological stress, cognitive overload, and reduced learning concentration. Although previous studies have extensively examined the relationship between financial stress and academic performance among university students, limited attention has been given to the financial management challenges experienced by mahasantri within Islamic boarding school ecosystems. This study aims to analyze the financial allocation patterns of mahasantri based on the Eisenhower Matrix framework and to examine behavioral changes and learning-related outcomes following the implementation of a priority-based financial management strategy. This study employed an exploratory qualitative approach with a pre-post observational design. Fifteen mahasantri from Darullughah Wadda’wah Islamic Boarding School and International Islamic University were selected using purposive sampling techniques. Data were collected through semi-structured interviews, consumption pattern observations, monthly budget reconstructions, and daily expenditure records over an eight-week period. The analysis was conducted by classifying respondents’ expenditures into the four quadrants of the Eisenhower Matrix to compare financial allocation patterns before and after the intervention. The findings reveal that, during the baseline phase, respondents’ expenditures were predominantly concentrated in Quadrant III (35%) and Quadrant IV (15%), reflecting socially driven and impulsive spending behaviors, while long-term educational investment in Quadrant II accounted for only 5% of total monthly allocations. Following the intervention, Quadrant II allocations increased significantly to 20%, accompanied by a reduction in Quadrant III expenditures to 15% and Quadrant IV expenditures to 5%. These behavioral changes were associated with reduced financial anxiety, improved cognitive stability, better access to learning resources, and enhanced continuity in muroja’ah (lesson review) and academic concentration.